2020
DOI: 10.1101/2020.11.25.397612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population genomics of the pathogenic yeast Candida tropicalis identifies hybrid isolates in environmental samples

Abstract: Candida tropicalis is a human pathogen that primarily infects the immunocompromised. Whereas the genome of one isolate, C. tropicalis MYA-3404, was originally sequenced in 2009, there have been no large-scale, multi-isolate studies of the genetic and phenotypic diversity of this species. Here, we used whole genome sequencing and phenotyping to characterize 77 isolates C. tropicalis isolates from clinical and environmental sources from a variety of locations. We show that most C. tropicalis isolates are diploid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 95 publications
(174 reference statements)
0
5
0
Order By: Relevance
“…This is also similar to the divergence between haplotypes in hybrids of C. orthopsilosis (Schröder et al . 2016) and C. tropicalis (O’Brien et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is also similar to the divergence between haplotypes in hybrids of C. orthopsilosis (Schröder et al . 2016) and C. tropicalis (O’Brien et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2016), and that C. albicans is an ancient hybrid (Mixão and Gabaldón 2020). However, rare hybrids of C. tropicalis are enriched in environmental, and not clinical sites (O’Brien et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast researchers' next steps include investigating how temperate forest yeast diversity has been shaped by dispersal and adaptation to changing environments across a long evolutionary time frame. Temperate forest yeasts are only a subset of yeast strains available in culture collections: Most of the available yeast isolates have instead been derived from fungal infections (O'Brien et al, 2021) or substrates that are related to human activities (Almeida et al, 2015; Gallone et al, 2016). Moreover, none of the model yeast species described in this review has been found among the most frequent species in environmental DNA from temperate forests, as reported in the GlobalFungi database.…”
Section: Future Perspectivesmentioning
confidence: 99%